Pengaruh Perencanaan Sumber Daya Manusia dan Budaya Organisasi terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Seluma - Imron Imron; Neri Susanti; Yesi Indian Ariska (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of this study was to determine the effect of human resource planning and organizational culture on employee performance at the Department of Population and Civil Registration of Seluma Regency. The sample in this study as many as 48 employees at the Department of Population and Civil Registration of Seluma Regency who have become ASN and honorary. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 0.868 + 0.547X1 + 0.448 X2+e, this describes a positive regression direction, meaning that there is a positive influence between X1 (HR planning) and X2 (organizational culture) on performance (Y). It means that if the variables of HR planning and organizational culture increase, it will increase performance. The value of the coefficient of determination is 0.602. This means that X1 (HR planning) and X2 (organizational culture) affect performance (Y) by 60.2% while the remaining 39.8% is influenced by other variables not examined in this study. HR planning has a significant effect on employee performance at the Department of Population and Civil Registration of Seluma Regency because the significant value of 0.000 is smaller than 0.05. Organizational culture has a significant influence on employee performance at the Department of Population and Civil Registration of Seluma Regency because the significant value of 0.010 is smaller than 0.05. The results of the F test at a significance level of 0.05 explain that the variables of HR planning and organizational culture have a significant simultaneous influence on employee performance at the Population and Civil Registration Office of Seluma Regency because the significant value of 0.000 is smaller than 0.05